Platelets in Sepsis: An Update on Experimental Models and Clinical Data - Assinger, Alice; Schrottmaier, Waltraud C.; Salzmann, Manuel; Rayes, Julie (Frontiers in Immunology, 2019)
Beyond their important role in hemostasis, platelets play a crucial role in inflammatory diseases. This becomes apparent during sepsis, where platelet count and activation correlate with disease outcome and survival. Sepsis is caused by a dysregulated host response to infection, leading to organ dysfunction, permanent disabilities or death. During sepsis, tissue injury results from the concomitant uncontrolled activation of the complement, coagulation and inflammatory systems as well as platelet dysfunction. The balance between the systemic inflammatory response syndrome and the compensatory anti-inflammatory response regulates sepsis outcome. Persistent thrombocytopenia is considered as an independent risk factor of mortality in sepsis, although it is still unclear whether the drop in platelet count is the cause or the consequence of sepsis severity. The role of platelets in sepsis development and progression was addressed in different experimental in vivo models, particularly in mice, that represent various aspects of human sepsis. The immunomodulatory function of platelets depends on the experimental model, time and type of infection. Understanding the molecular mechanism of platelet regulation in inflammation could bring us one step closer to understand this important aspect of primary hemostasis which drives thrombotic as well as bleeding complications in patients with sterile and infectious inflammation. In this review, we summarize the current understanding of the contribution of platelets to sepsis severity and outcome. We highlight the differences between platelet receptors in mice and humans and discuss the potential and limitations of animal models to study platelet-related functions in sepsis.